Modern and effective energy-saving technology (Journal of Geography and Environmental Management, 2017)
The article deals with basic modern energy saving technologies used in industry, construction and transport industries in an ever-growing energy deficit. Тhe authors identified the environmental and economic advantages of using energy-saving technologies such as the installation of energy-saving roof, the use of energy-saving paints, wall insulation, double glazing, modern, high-tech and economical heating and cooling. The advantages and disadvantages of different types of building ventilation systems (mechanical, personalized, hybrid) in terms of energy saving. A brief description of modern boilers, the installation of which is a promising trend in the use of energy-saving technologies. The prospects of change in the traditional scheme of heat supply in the transition from individual to central heating. It is also considered the possibility of using innovative technologies in energy saving, namely: overhead infrared heaters and radiant heating systems in housing and communal services. The use of any of these technologies entail positive environmental effects associated with the saving of fuel resources and reduction of anthropogenic emissions of greenhouse gases and polluting emissions through the introduction of new energy-saving technologies and equipment in the production of these industries.